Case study of C.I Holdings Berhad market performance from the year 2006 to 2009 / Mohd Khairi Azri Yusoff - Yusoff, Mohd Khairi Azri (Faculty of Business and Management, 2009)
The aim of this study is to investigate the market performance of the C.I Holdings Berhad C.I. Holdings Berhad is a Malaysia-based company engaged in investment holding and the provision of management services to its subsidiaries. The Company is organized into three business segments: beverages, building and construction-related products and investment holdings. This report is to identify and investigate C.I Holdings Berhad financial performance for four years back, from year 2006 until year 2009. The analysis of the C.I Holdings Berhad financial performance will be related to the fundamental analysis. The findings will be presented in three main issues. Firstly the researcher will analyze how C.I Holdings Berhad revenue trends are for the past 4 years and what is the performance of key stock statistic of C.I Holdings Berhad. Finally, the researcher will identify how the price movement of the C.I Holdings Berhad.